Answer:
[tex]\displaystyle f(b+2) = 2b^2 + 11b +6[/tex]
Step-by-step explanation:
We are given the function:
[tex]\displaystyle f(x) = 2x^2 + 3x - 8[/tex]
And we want to find:
[tex]\displaystyle f(b + 2)[/tex]
Substitute:
[tex]\displaystyle f(b+2) = 2(b+2)^2 + 3(b+2) - 8[/tex]
Expand and simplify:
[tex]\displaystyle \begin{aligned}f(b+2)&= 2(b^2+4b+4)+(3b+6)-8 \\ &= (2b^2+8b+8)+(3b+6)-8 \\ &= (2b^2) + (8b+3b)+ (8+6-8) \\ &= 2b^2 + 11b + 6 \end{aligned}[/tex]
In conclusion:
[tex]\displaystyle f(b+2) = 2b^2 + 11b +6[/tex]